About aspects of economic technique of ascent the routes in the discipline of sport climbing «lead» - Olexii Shulha (Kharkiv State Academy of Physical Culture, 2015)
Purpose: definition of parameters technique of motor actions athletes climbers, reflecting efficiency of the work in the discipline of climbing «lead». Material and Methods: the video resource official website of the International Federation of Sport Climbing (IFSC). Results: Pace and rhythmic structure of movement technique of elite athletes-climbers in a competitive activity were analyzed. Parameters of hand-movement pace while climber ascent the route, as well as the ratio of the different contact phases of interaction of hands with handholds were determined. Conclusion: the economic of technique movement while climber ascent the route dictated by the pace of hand-movements and the prevalence in the ratio of the rhythmic structure contact phase with one hand was found.